Detecting Convergence Trends among EU Universities - Maria Adamakou; Dimitris Kallioras; George Petrakos (Economies, 2021)
Universities are emerging growth determinants. This is so as, in addition to the fulfillment of their traditional role in teaching and (basic) research, universities, as aptly described within the helix framework, are expected to engage in regional development processes. The paper aims to detect trends of convergence among EU universities in terms of performance. To the best of our knowledge, this topic has not hitherto been examined. The empirical analysis of the paper covers the period 2014–2021, utilizes data obtained from URAP (University Ranking by Academic Performance), and employs the methodological approach of convergence clubs. The findings of the paper provide valuable insight into both theory and policy-making. We conclude that despite the unification of EU educational space, trends of divergence among EU universities are still present, and notable divisions still remain. Consequently, this indicates that the impact of EU universities on the formation of spatial disparities across EU space is not neutral.